The Single Market and EU Competition Law - Two Pillars of the European Union - LUCIA IORDACHE (Global Economic Observer, 2014)
The interplay between a deeper, broader, well-functioning Single Market and an active and efficient enforcement of EU competition law is at the core of higher productivity and sustainable growth across Europe. This paper focuses on the domains in which competition policy can help to create and consolidate a genuine Single Market and capitalize on the full potential for Europe’s competitiveness in a globalised world. In competition matters, the European Commission has more power than in any other policy areas, with its combined roles as initiator of European legislation and as competition enforcer. The modernisation of the competition policy and law enforcement has been the result of the EU political, economic and social agenda. The European Commission is leading this process, which is the main lever the Union has to respond to the multiple challenges ahead – the globalisation of business and the evolution of the financial and economic crisis.